Islamic Governance in Village Financial Management in Indonesia: Lessons from Lobuk Village of Madura Island - Setiawan, Achdiar Redy; Yusoff, Murni Yusoff (Jurnal Dinamika Akuntansi dan Bisnis, 2025)
This research aims to integrate an Islamic governance framework into Village Financial Management (VFM) that can be applied across village governments in Indonesia. Using an ethnomethodological approach, this study was conducted in the village government of Lobuk, located on Madura Island. Data were collected from observation and in-depth interviewees with village government apparatus between July 2023 and January 2024. The empirical findings are then compared with these Islamic principles and elements to develop a model of Islamic (good) governance for VFM. The findings revealed three core principles, seven Islamic elements, and one overarching goal of VFM, symbolically represented through a mosque structure, comprising a foundation, pillars, and a roof. The proposed Islamic governance model for VFM, offers a comprehensive and foundational solution to address the misuse of village financial resources in Indonesia.